GENERASI Z: INSTAGRAM DAN DA’I - Mohamad Syafri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This research studies how the Z generation at IAIN Palu in terms of activeness on Instagram social media, as well as how they see religious leaders. Research focusing Instagram social media refers to the level of popularity of Instagram in Z generation. This research was conducted using a survey design that was carried out thoroughly with a sample of 222 people. Research shows there are differences in choosing da'I and religious leaders between those who actively use social media Instagram and those who do not use Instagram. The results of this study indicate the need for more in-depth studies related to social media in terms of its function as one of the dakwah media. Especially seeing the high public interest in using social media.